Preparing The Youth In Achieving The Goal Of " Health For All By 2000 Ad" : An Experiment - Singh Bir; Bharel Bharel; Amar Shanta (Wolters Kluwer Medknow Publications, 1986)
This article deals with an experiment presently being carried out by N.S.S Unit, at Center for Community Medicine, A.I.I.M.S. Non- medical N.S.S Volunteers of Delhi University are being trained for five days in basic aspects of Community Health. The results of the training are very encouraging. The authors feel that these types of training programme can be taken up by N.S.S. Units of various medical colleges through Department of Community Medicine in building up a force of youth who can act as messengers for spreading the messages of health in the Community & thus helping in their own way in achieving the goal of â€ Health for all by 2000ADâ€